Biology and Management of Torpedograss (Panicum repens) in Ornamental Landscape Planting Beds - Yuvraj Khamare; Candice Prince; Chris Marble (EDIS, 2021)
Torpedograss is one of the most invasive perennial grass species in Florida landscapes. This new 5-page publication of the UF/IFAS Environmental Horticulture Department was written for green industry professionals and others to aid in the identification and management of torpedograss in landscape planting beds. Written by Yuvraj Khamare, Candice Prince, and Chris Marble. https://edis.ifas.ufl.edu/ep615